Heavy metal remediation : transport and accumulation in plants - Gupta, Dharmendra Kumar (Phytoremediation researcher); Chatterjee, Soumya (New York : Nova Publishers, 2014)
Plants have a very specific and efficient mechanism to obtain, translocate and store nutrients from the surrounding environment. The precise mechanism that helps a plant in nutrient translocation from root to shoot also, in the same way, transfers and stores toxic metals within their structure. Metal toxicity generally causes multiple direct or indirect effects on plants, affecting nearly all of their physiological functions. Plant tolerance to heavy metals depends largely on plant efficiency in uptake, translocation and sequestration of heavy metals in specific cell organelles or specialized.
2.9. Arsenic Effects on Physiological Processes2.9.1. Photosynthesis; 2.9.2. Antioxidant Enzymes; 2.9.3. Mineral Nutrition; 3. Chromium; 3.1. Chromium Uptake; 3.2. Chromium Metabolism; 3.2.1. Chromium Association with Thiol Compounds; 3.2.2. Chromium Accumulation and Translocation; 3.3. Toxic Effects of Chromium on Plants; 3.3.1. Chromium Effects on Germination; 3.3.2. Chromium Effects on Root and Shoot Growth; 3.4. Chromium Effects on Physiological Processes; 3.4.1. Photosynthesis; 3.4.2. Antioxidant Enzymes; 3.5. Water Relations and Mineral Nutrition; 3.6. Other Biochemical Effects.
Includes bibliographical references and index.
Description based on print version record.
Master record variable field(s) change: 050, 082
Keywords: Phytoremediation; Plants -- Effect of heavy metals on; Heavy metals -- Environmental aspects; TECHNOLOGY & ENGINEERING -- Environmental -- General; Heavy metals -- Environmental aspects; Phytoremediation; Plants -- Effect of heavy metals on; 7 -- Electronic books